Literary Mama : Reading for the Maternally Inclined. - Buchanan, Andrea J. (Seal Press, 2005)
Becoming a mother takes more than the physical act of giving birth or completing an adoption: it takes birthing oneself as a mother through psychological, intellectual, and spiritual work that continues throughout life. Yet most women's stories of personal growth after motherhood tend to remain untold. As writers and mothers, Andrea Buchanan and Amy Hudock were frustrated by what they perceived as a lack of writing by mothers that captured the ambiguity, complexity, and humor of their experiences. So they decided to create the place they wanted to find, with the kind of writing they wanted to.